O abuso do poder religioso eleitoral: constitucionalismo e legitimação - Souza, Rogério da Silva e (2020)
The study deals with the confrontation of the abuse of religious power in the electoral process and the discourse of confessional legitimation in the common space, based on a constitutional reflection on alterity. The research aims to understand the abusive phenomenon of faith in elections, pervaded in the postmodern condition and how the constitutionalism of alterity can go against the abusive form with a focus on the moral reflection of the constitutional subjects. First, a discursive analysis of constitutional absenteeism was made, as a relationship between the State and religious institutions, in the Brazilian historical-political experience, and the proposal of constitutionality of alterity was constructed, as a narrative of moral legitimation about the place of the other to demand the responsibility for the abuse of religious power in electoral affairs. The constitutional discourse of alterity was also compared in the face of two paradigmatic precedents of the Superior Electoral Court, given the rise of the theme in the Regional Electoral Courts, to then proceed, based on constitutional alterity, to a conjunctive prognosis of tasks to combat the abuse of faith in the political-jurisdictional scenario of the country. The phenomenon of the abuse of religious power in the constitutional spectrum was analyzed with the thematic focus coming from electoral colleges, following this pitch, the jurisprudence of the Regional Courts was established in view of the precedents of the Superior Electoral Court: the first precedent signaled an eventual change in the thinking of the country's electoral court; and the second precedent presented the jurisprudential mutation established on the abuse of religious power in the elections as a hypothesis of economic abuse. Criticism of political reforms and jurisdictional arguments was also confirmed, based on constitutional alterity and the intentional-consequence logic, in the face of the abusive phenomenon of faith in elections. It was concluded that although the State seeks the discourse of absenteeist secularization in the intersubjective field, the narrative of constitutional neutrality in matters of faith has not been consolidated, leaving a moral crisis in constitutionalism in the face of responsibility for the place of the other, at the time when the Electoral jurisdiction gauges and combats the ungodly way in which some religious entities appropriate the electoral process with manifest institutional and economic abuse of the faith on the democratic space.